A bibliometric and Visualized Analysis of Financial, Economic and Technological Factors Affecting the Environmental Sustainability - Muhammad Naeem Shah; Muhammad Sadiq Shahid (Journal of Accounting and Finance in Emerging Economies)
Purpose: Financial, Economic and Technological Factors play key role in Environmental Sustainability. This paper aims to analyze the existing research on factors affecting the Environmental Sustainability through a bibliometric approach.